Some features of transverse photovoltage in semiconductor heterostructure and Schottky contact - Shekhovtsov, L.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2001)
We investigated transverse photovoltage generated in semiconductor heterostructures by a modulated illumination. A complicated form of the photovoltage spectral curves for Ge-GaAs heterostructures and NbN-GaAs Schottky contacts is determined by interaction between photocurrents flowing in the bulk and near interfaces.

An additional unmodulated illumination of the samples during the measurements of the photovoltage spectral curves changes the interaction of photocurrents. This leads to modification of the photovoltage spectral curves. An analysis of their features enables one to put forward models for interaction of photocurrents flowing near the interfaces and obtain the characteristics of the interface uniformity in composite semiconductor structures.